A Review on Analysis Search Based Software Testing using Metaheuristics Techniques - Kumar, Mandeep; Nandal, Deepak (International Journal of Computer Sciences and Engineering, 2025)
Search-Based Software Testing (SBST) is a form of Search-Based Software Engineering (SBSE) to optimize testing through the use of computational search. Search Based Software Testing (SBST) denotes process of meta-heuristics for optimization of task into perspective of software testing. The expenditure of meta-heuristics analysis activities are accomplished for upper numbers of inputs that essential to be verified. In this paper we explain how we created an efficient testing techniques to compare searches based Meta heuristics algorithms based on their parameter and get their performance and test them.These Algorithms are used to generate automatic test data that satisfy branch coverage, path coverage, cost and time and quality in software testing. Cost of testing behavior has primary section of the total cost of software. Finally, this paper present the result which carried out to estimate the efficiency of the proposed techniques with new fitness function compared to each other based on their parameters and analyses the performance. SBST for test Generation, efficient MetaHeuristics search Algorithms.